2020
DOI: 10.3390/ijms21051883
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage-Insensitive Mutants of Antimicrobial-Resistant Salmonella Enterica are Altered in their Tetracycline Resistance and Virulence in Caco-2 Intestinal Cells

Abstract: Bacteriophages have shown promise as therapeutic alternatives to antibiotics for the control of infectious bacteria, including the human pathogen Salmonella. However, the development of effective phage-based applications requires the elucidation of key interactions between phages and target hosts, particularly since host resistance to phage is inevitable. Little is known about the alteration of host phenotypes following the development of resistance to phage. The aim of this study is to evaluate the antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Interestingly, we found that no stable phage-resistant mutants appeared for both the phages studied as regrowing bacterial cells lost resistance to phage with a maximum of two serial passages, thus showing the presence of transient phage resistant mutants. Similar observations were noted in Salmonella enterica by Fong et al, in which most of the transient phage-resistant mutants isolated become susceptible to serial passage (Fong et al 2020).…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, we found that no stable phage-resistant mutants appeared for both the phages studied as regrowing bacterial cells lost resistance to phage with a maximum of two serial passages, thus showing the presence of transient phage resistant mutants. Similar observations were noted in Salmonella enterica by Fong et al, in which most of the transient phage-resistant mutants isolated become susceptible to serial passage (Fong et al 2020).…”
Section: Discussionsupporting
confidence: 83%
“…As a result, a number of trade restrictions are introduced in cases where there is contamination with prevalent serotypes of S. Enteritidis and S. Typhimurium leading to major loss of income to farmers and producers due to rejection of substandard contaminated animal products ( Majowicz et al, 2010 ; Kirk et al, 2015 ; EFSA Panel on Biological Hazards et al, 2019 ). Although antibiotics are useful in controlling the infection in both humans and animals, many of the bacterial strains are becoming resistant to routinely used antibiotics leading to treatment failure and disease outbreaks ( O’Neil, 2014 ; Fong et al, 2020 ). As the identification and development of new antibiotics is slow and difficult, the associated economic and social loss highlight the pressing need to develop alternative more effective therapeutics for this infection ( O’Neil, 2014 ; Romero-Calle et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The growing inadequacy of antibiotics has paved the way for novel therapies that rely on antibiotic alternatives. Many studies have focused on application of lytic phages for direct killing of their bacterial hosts, however, host resistance still occurs (Fong et al, 2017(Fong et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%